Did the 2008 Tax Rebates Stimulate Spending? - Shapiro, Matthew D; Slemrod, Joel (American Economic Review, 2009)
In an effort to bolster economic performance in light of a looming downturn in economic activity, on February 13, 2008, President George W. Bush signed the Economic Stimulus Act of 2008. More than two-thirds of the $152 billion bill consisted of economic stimulus payments to be sent beginning in May to approximately 130 million households. To qualify, recipients had to have a valid Social Security number, an income tax liability, or at least $3,000 of “qualifying income” that included earned income and some benefits from Social Security, Veterans Affairs, or Railroad Retirement, and have filed a 2007 federal tax return. For the most part those who filed as single individuals received between $300 and $600, while those who filed jointly received between $600 and $1,200. Additionally, parents with children under 17 who were eligible for a Child Tax Credit and had a Social Security number received an extra $300 per child. The tax rebate phased out at higher levels of income, as the payment was reduced by 5 percent of the amount of adjusted gross income over $75,000 for singles, or over $150,000 for married couples. The Treasury remitted payments either by direct deposit, mainly in the first half of May, or by mail, mainly from mid-May through mid-July. The effect of these stimulus payments depends on how much was spent. This paper reports new survey evidence on the propensity of consumers to spend the 2008 rebate. It also relates the survey evidence to aggregate data and to evidence about spending from the 2001 tax rebate.